Heritability estimates of egg weight and egg shell weight in Ikenne, Nigeria - John-Jaja, Sylvia; Abdullah, Abdur-Rahman; Nwokolo, Samuel (International Journal of Scientific World, 2017)
This study is designed to determine the inheritance pattern of egg weight and egg shell weight of exotic laying chickens at 25, 51, 72 weeks and overall mean ages of the birds. For this purpose, thirty eggs were collected daily from the birds continuously for five days of egg production, at each ages 25, 51 and 72 weeks. The total number of eggs collected at each age was 150 and 450 for the total of three age periods. The mean values of egg weight and egg shell weight revealed an apparent increase from 25-72 weeks of age with their corresponding overall mean values. The least square means of egg shell weight at different age groups are significantly different at (P<0.01) while egg weight was significantly the same since egg shell weight depends on age variance for adequate performance. Statistical analytical system was used to obtain the variance components for the estimation of heritability. High and moderate heritability estimates were obtained when the age variance were included in the computation at different age groups for both traits while high, moderate and low estimates were obtained when the age variances were excluded. The heritability estimates from different egg quality traits were low to high. Since egg weight yielded high estimates at various age groups, the low and moderate heritability estimates recorded for egg shell weight imply that collection of additional records and improvement of non-genetic factors influencing the trait will improve the accuracy of characterizing the inherent ability of the birds.